2019
DOI: 10.1111/pce.13535
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene is more affected by climate drivers than monoterpenes: A meta‐analytic review on plant isoprenoid emissions

Abstract: Isoprene and monoterpenes (MTs) are among the most abundant and reactive volatile organic compounds produced by plants (biogenic volatile organic compounds). We conducted a meta‐analysis to quantify the mean effect of environmental factors associated to climate change (warming, drought, elevated CO2, and O3) on the emission of isoprene and MTs. Results indicated that all single factors except warming inhibited isoprene emission. When subsets of data collected in experiments run under similar change of a given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 79 publications
2
59
0
Order By: Relevance
“…likely because of high anthropogenic emissions that undermine the feedback of IPE changes to surface O 3 . However, the reduced IPE weaken SOA radiative forcing and increase surface temperature in the eastern US, where biogenic SOAs provide important contributions to total aerosols (Fine et al, 2008;Goldstein et al, 2009). These results suggest that IPE feedback to the surface O 3 is quite uncertain and dependent on ambient precursors (anthropogenic vs. biogenic) and oxidizing capacity (NO x -saturated vs. NO x -limited).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…likely because of high anthropogenic emissions that undermine the feedback of IPE changes to surface O 3 . However, the reduced IPE weaken SOA radiative forcing and increase surface temperature in the eastern US, where biogenic SOAs provide important contributions to total aerosols (Fine et al, 2008;Goldstein et al, 2009). These results suggest that IPE feedback to the surface O 3 is quite uncertain and dependent on ambient precursors (anthropogenic vs. biogenic) and oxidizing capacity (NO x -saturated vs. NO x -limited).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…In this work, Arabidopsis plants transformed to emit constitutively isoprene or ocimene were compared for the first time and a comprehensive shoot characterization was carried out in order to assess their potential role on stress tolerance and plant growth. The comparative approach used in our study has two major advantages with respect to similar studies carried out in the past in different species [31]. First, it compared in the same genetic background the physiological effects of isoprene and ocimene emission, thus normalizing the effect of the starting pool of metabolites, which is known to vary among species and affect emissions [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of IPE changes is generally within the range of 10-29%, as summarized by the observational meta-analysis (Feng et al, 2019b). The F scheme is dependent on instantaneous O3 uptake, which peaks during the summer when both surface O3 and stomatal conductance are high.…”
Section: Offline O3 Damage To Ipementioning
confidence: 97%
“…Several studies have showed that O3 fumigation over a short time (days to weeks) but at high concentrations (100-300 ppbv) led to increased IPE (Velikova et al, 2005;Fares et al, 2010), while some other experiments conducted over an entire growing season (at least 3 months) under controlled O3 concentrations (approximately 25 80 ppbv) showed that O3 reduced IPE (Calfapietra et al, 2008;Yuan et al, 2016;Yuan et al, 2017). A recent global metaanalytic review showed that IPE negatively responded to elevated O3 (91 ppbv on average) by -8% (Feng et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%